Association Of Obese and Morbidly Obese Status with Hypoalbuminemia in Adults Without Liver and Kidney Disease: Obese and Morbidly Obese Status with Hypoalbuminemia in Adults - Maqsood, Muhammad; Iram, Husna; Mariyam Haroon, Sundus; Salman, Sadia; Bhalli, Amanullah; Iqbal, Sadaf (Pakistan Journal of Health Sciences, 2022)
Obesity is an excessive accumulation of fat in the body and is measured in terms of increased body mass index. Its prevalence is increasing in all age groups and is now considered to be a global epidemic. Albumin is the most abundant plasma protein synthesized in the liver and is customarily utilised to detect malnourishment and severe starvation. It is one of the poor prognostic factors in medical, surgical, and critically ill patients. Objective: To identify the relationship between obesity and morbid obesity and hypoalbuminemia in adults in Pakistan with no signs of liver or kidney disease. Methods: Jinnah Allama Iqbal Institute of Diabetes and Endocrinology (JAIDE), Jinnah Hospital Lahore Pakistan, was chosen for the completion of this cross-sectional study with a time frame of October 2019 to April 2020. 90 patients, ranging between ages of 18 and 70 years, without liver and kidney diseases, were recruited and were divided into three categories, healthy control, obese, and morbidly obese on the basis of BMI. Venous blood samples for albumin were taken. Results: The percentage of hypoalbuminemia was 10.0% in healthy controls, 40.0% in the obese group, and 46.7% in morbidly obese. Hypoalbuminemia rate was significantly higher in obese and morbidly obese groups (p-value 0.005) as compared to healthy controls, independent of age, sex, and diabetes. Conclusions: Upon completion of this study, it was concluded that the morbid obesity and obesity are the independent forecasters of hypoalbuminemia.